Кристалічна структура шаруватого ніобатоцирконату Sr₆Nb₄ZrO₁₈ - Тітов, Ю.О.; Білявина, Н.М.; Слободяник, М.С.; Полубінський, В.В.; Чумак, В.В. (Доповіді НАН України, 2016)
За керамiчною технологiєю (прекурсори — чотиришаровий Sr₅Nb₄O₁₅+перовськiт SrZrO₃, T = 1670 K) синтезовано п’ятишаровий нiобатоцирконат Sr₆Nb₄ZrO₁₈ та методом рентгенiвської дифракцiї на порошку визначено його шарувату перовськiтоподiбну структуру (ШПС). Встановлено належнiсть ШПС Sr₆Nb₄ZrO₁₈ до структурного типу Ba₆Nb₄TiO₁₈. Параметри елементарної комiрки Sr₆Nb₄ZrO₁₈: a = 0,5687(1) нм, c = 4,146(1) нм, просторова група R−3m, значення фактору недостовiрностi RB дорiвнює 0,055. Проаналiзованi особливостi ШПС Sr₆Nb₄B^IVO₁₈ (B^IV = Ti, Sn, Zr) i встановленi взаємозв’язки склад — будова ШПС. По керамической технологии (прекурсоры — четырехслойный Sr₅Nb₄O₁₅+перовскит SrZrO₃, T = 1670 K) синтезирован пятислойный ниобатоцирконат Sr₆Nb₄ZrO₁₈ и методом рентгеновской дифракции на порошке определена его слоистая перовскитоподобная структура (СПС). Установлена принадлежность СПС Sr₆Nb₄ZrO₁₈ к структурному типу Ba₆Nb₄TiO₁₈. Параметры элементарной ячейки Sr₆Nb₄ZrO₁₈: a = 0,5687(1) нм, c = 4,146(1) нм, пространственная группа R−3m, значение фактора недостоверности RB составляет 0,055. Проанализированы особенности СПС Sr₆Nb₄B^IVO₁₈ (B^IV = Ti, Sn, Zr) и установлены взаимосвязи состав — строение СПС. Five-layer niobatozirconate Sr6Nb4ZrO18 has been synthesized by the ceramic technology (presynthesized reagents — four-layer Sr₅Nb₄O₁₅ + perovskite SrZrO₃, T = 1670 K), and its layered perovskite-like structure (LPS) is determined by the method of X-ray powder diffraction. It is found that the LPS of Sr₆Nb₄ZrO₁₈ belongs to the Ba₆Nb₄TiO₁₈-type structure. The parameters of the elementary cell of Sr₆Nb₄ZrO₁₈: a = 0.5687(1) nm, c = 4.146(1) nm, space group R−3m, the value of the reliability factor RB is equal to 0.055. The peculiarities of Sr₆Nb₄B^IVO₁₈ (B^IV = Ti, Sn, Zr) LPS are analyzed, and the correlations composition — constitution of LPS have been established.